P- 56 Tuberculosis in liver transplant recipients: experience of a single center - Bertha, Cárdenas Ramírez (2024)
In Peru the tuberculosis (TB) is an endemic infectious disease. This disease is a serious opportunistic infection in transplant recipients (LTRs) and has 20 to 74-fold increase in a chance of developing compared to the general population The prevalence of TB in (LTRs) is variable between regions. This study aims to describe the rate, clinics characteristics and mortality of TB in LTRs from a high-prevalence area.